Study of Molecular Docking of Alkaloid Derivative Compounds from Stem Karamunting (Rhodomyrtus tomentosa) Against α-glucosidase Enzymes - mulyati, Budi; Seulina Panjaitan, Riong (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2021)
Karamunting plant (Rhodomyrtus tomentosa) is a traditional medicinal plant. The leaves, roots, stems, and fruits of Karamunting have been identified, and their biological activities are antioxidants, antibacterial, antidiabetic, anti-inflammatory, and anticancer that contained alkaloids, tannins, and flavonoids. The types of alkaloids found in karamunting stems are homolycorine, ismine, lycorine, maritidine and tazetine. This study aims to determine the binding score of alkaloid-derived compounds with protein α-glucosidase and determine the protein's active site bound to the ligand. The method used in this research is Protein-Ligand ANT-System (PLANTS). The results showed that the anchoring score of homolycorine was -60.83 kcal/mol, ismine -64.42 kcal/mol, lycorine -71.20 kcal/mol, maritidine -61.82 kcal/mol, and tazetine -65.02 kcal/mol. The active sites used for binding are Glu526, Gly555, and Pro556. The average score for anchoring alkaloid-derived compounds with protein Î±-glucosidase is 83.84%. This number indicates that karamunting stems can be used as antidiabetic.